Dosage Modification of Traditional Chinese Medicine Prescriptions: An Analysis of Two Randomized Controlled Trials - Zhou, Rongrong; Zheng, Yujiao; An, Xuedong; Jin, De; Lian, Fengmei; Tong, Xiaolin (Frontiers in Pharmacology, 2021)
Traditional Chinese medicine (TCM) prescriptions lack standardization due to the complex composition of the prescribed herbs, the unclear mechanism of the formulas, and a lack of scientific data to support the dose-response relationship. Here, we proposed a new clinical strategy of dosage modification for TCM prescriptions to evaluate the clinical efficacy and guide the clinical medication. This study used two TCM prescriptions for the treatment of newly diagnosed Type 2 diabetes mellitus (T2DM) to explore the key indications and the most appropriate critical values of dosage modification by analyzing two randomized controlled trials (RCTs). In Study 1, the correlation analysis between the change range of indicators at three time points (weeks 4, 8 and 12) from baseline and the decrease in HbA1c at week 12 from baseline (HbA1c 012) was carried out to screen the related indications. Next, we evaluate the related indications and the respective critical values to determine the key indicators, indications, and the most appropriate critical value. We conducted a correlation between the change range of key indicators (obtained from the result of Study 1) at three time points from baseline and HbA1c 012 to screen the key indications in the drug group, high-dose group, and low-dose group in Study 2. Key indications with critical values were determined to investigate the most appropriate critical value in the three groups separately. In Study 1, the key indicator was FBG, the key indication was FBG 04, and the most appropriate critical value was 0.5 mmol/L. In Study 2, the key indication was FBG 04 and the most appropriate critical value was 0.6 mmol/L in the drug group. In the high-dose group, the key indication was FBG 04, and the most appropriate critical value was 0.3 mmol/L. In the low-dose group, the key indication was FBG08, and the most appropriate critical value was 0.1 mmol/L. In addition, we summarized a verification strategy for dosage modification.